Pyrolysis or hydrothermal carbonisation for anaerobic-digested sewage sludge? A comparison of pyrochar and hydrochar structure and stability - Pimenta-Ocampo, Maria; Gascó, Gabriel; Mendez, A.; Otten, Wilfred; Sakrabani, Ruben (Springer, 2024)
Thermochemical conversion of sewage sludge was proven as a useful method for waste management. Moderate temperatures in the absence of oxygen (pyrolysis) and hydrothermal carbonisation (HTC) performed in the presence of water, under autogenous pressures, were selected to treat the same sample of anaerobic-digested sewage sludge (SS). Two hydrochars were prepared by HTC in one high-pressure reactor using SS at 80% humidity content and heating it at 180 and 240 °C for 4 h, leading to H180-4 and H240-4, respectively. Two pyrochars were prepared from a pre-oven-dried SS at 105 °C for 48 h, followed by slow pyrolysis at 300 °C for 1 h, and 400 °C for 1 h leading to P300-1 and P400-1, respectively. HTC and slow pyrolysis significantly increased thermal stability of chars with higher temperatures, only reducing organic matter content (from 68.4 to 46.7–59.2%). Based on the characterisation results, the treatments could be a suitable choice to pre-treat sludge as soil amendment. Higher temperatures of pyrolysis would be attractive to store stable carbon in soil and construction materials, whilst lower temperatures of pyrolysis and HTC would produce a material that could be used as a source of organic matter providing a pool of labile carbon and fixed carbon. Thermochemical conversions generated mesopores (10–50 nm, >40%) and slightly increased surface area from 2 m2/g (SS) to 5–17 m2/g (pyrochars) and to 20 m2/g (hydrochars). Hence, HTC showed the greatest potential to produce a material with higher adsorption capacity (100 cm3/g for H180-4) but all chars should be subjected to an activation process to be able to compete with other kinds of feedstocks. The reduction of the H:C and O:C from the original SS after the treatments indicated a greater carbonisation degree, but a general reduction of the high heating value (HHV) from 17.94 MJ kg−1 in SS to (14.93 MJ kg−1). The torrefied char and hydrochars could be an attractive option to reduce energy of the process and drying stage in the case of HTC.
Keywords: Sewage sludge; Biosolids; Hydrothermal carbonisation; Lower classed biochar; Pyrochar; Hydrochar